Functional Organ Preservation Surgery in Head and Neck Cancer: Transoral Robotic Surgery and Beyond - Golusiński, Wojciech (Frontiers in Oncology, 2019)
In recent years, interest in functional organ preservation surgery (FOPS) in the treatment of head and neck cancer has increased dramatically as clinicians seek to minimize the adverse affects of treatment while maximizing survival and quality of life. In this context, the use of transoral robotic surgery (TORS) is becoming increasingly common. TORS is a relatively new and rapidly-evolving technique, with a growing range of treatment indications. A wide range of novel, flexible surgical robots are now in development and their commercialization is expected to significantly expand the current indications for TORS. In the present review, we discuss the current and future role of this organ-preserving modality as the central element in the multimodal treatment of head and neck cancer.